ANALYS FINANCIAL FEASIBILITY OF KOI FISH SALES BUSINESS IN JAVA KOI CENTER, CIMAHI CITY, WEST JAVA - Alim Dhia Ubaidillah; Ine Maulina; Dian Yuni Pratiwi; Atikah Nurhayati (Jurusan Perikanan dan Kelautan, 2023)
Java Koi Center is one of the largest local koi carp business in Cimahi City. This research aims to analyze the financial feasibility of Java Koi Center, Cimahi City, West Java. This research uses a quantitative descriptive analysis. The data collected in this study are aspects that exist in business feasibility and the main thing is the financial aspect. In the financial aspect, the data studied are business capital, investment costs, operational costs, Revenue Cost Ratio (R/C) and Break Even Point (BEP). To analyze financial feasibility, investment assessment criteria are used including Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C) and Payback Period (PP). Based on data analysis, it was obtained that the R/C value was 1.90 and Break Even Point was obtained BEP Sales Mix for Kohaku koi totaling 23 heads with total sales of Rp28.716.952, Sanke koi was 21 heads at a price of Rp18.796.550, Hi-utsuri totalling 15 heads with a price of Rp13.157.584, Bekko koi fish was totalling 13 heads at a price of Rp7.518.620 and Sushui koi fish 17 heads at a price of Rp10.024.827. In the calculation of financial feasibility analysis, NPV value was obtained at Rp275,228,463, IRR value of 81%, Net B/C value of 3.07 and the Paypack Period for 1.17 years. So from the results of this research, Java Koi Center business is very feasible and profitable to run and develop in the future.